Obstacles Facing the Implementation of Internal Quality Systems in the Departments of the Faculty of Education, Umm Al-Qura University - Hayat Mohammad Saad Alharbi (University of Science and Technology, Yemen, 2019)
The study aimed to identify the level of obstacles facing the implementation of the internal quality systems in the departments of the faculty of education at Umm Al-Qura university from the point of view of the faculty members; to identify the most significant obstacles affecting these systems; and to determine whether there were statistically significant differences between the means of the participants' responses attributed to these variables: (gender, job title and academic rank). To achieve these objectives, the descriptive analytical method was used and a questionnaire was administered to collect data from a sample of (103) quality officials and faculty members. Major results revealed that the participants' degree of assessment was medium with a mean of (3.04). Human obstacles came in the first rank, obstacles related to the educational program second, administrative and financial obstacles third, and obstacles of the formation of the internal system were in fourth rank. The study also showed that (22) obstacles had the highest effect on the internal quality systems according to Pareto chart. There were statistically significant differences between the mean responses of the participants regarding the variables (gender, academic rank), but no differences were shown regarding the variable of job title. It was recommended that the Faculty of Education should raise the efficiency and effectiveness of the internal quality systems by reorganizing and restructuring the systems, to provide adequate support for quality efforts and to spread quality culture and practice in daily activities. Keywords: quality obstacles, internal quality system, Faculty of Education.